A sink based data gathering technique by using clustering for wireless sensor networks - Yousra Abdul Alsahib S. Aldeen; Haider Mohammed Abdulhadi (Universitas Ahmad Dahlan, 2022)
New advance and integrated technologies have changed the traditional systems and convert these systems into more intelligent, feasible and cost effective systems. In all data communications domain, data gathering is one of the significant task performed by using any techniques, tools and devices. Wireless sensor networks (WSN) also gained popularity in various fields where the sensor node sensed the information by using sink or gateway nodes and further send to central units for decision making. With passage of time, these networks have faced complexities where most of the existing techniques have suffered with load balancing, complex processes, overhead and energy consumption issues. Firstly, this paper provides detail comparison of existing data gathering techniques adopted for WSN and then provides their performance analysis. After comparison, this paper proposes a novel data gathering techniques called a sink based data gathering techniques (ASDG) to collect the data from the sensor nodes and further send for decision making. Experimental results show that proposed techniques is better than existing techniques and provide more efficient data delivery ratio with more network lifetime. The results also indicated that when using the proposed technique, the no of dead sensor nodes are less as compared to the existing ones at different rounds.